Safeguarding Children's Well-Being: Voices From Abused Mothers Navigating Their Relationships and the Civil Courts. Issue 9 (May 2021) - Miller, Susan L.; Manzer, Jamie L.
Battered mothers often go to great lengths to protect their children from abuse. Most of these efforts play out in private settings such as the home. After their relationships end, women's actions shift to the public sphere for judgment by the courts. Abusers' strategies utilize the courts as another tool with which to call into question and challenge their former partners' parenting. Images of "good mothers" who behave passively are favored by officials who often have incomplete understandings of the dynamics of intimate partner violence and abuse. Existing studies about justice-involved mothers insufficiently portray women's experiences managing both continued abuse from past partners as well as discriminating treatment by the courts. Semistructured interviews with 25 women in the United States who have terminated their abusive relationships reveal strategies of negotiation and resistance used to protect their children both during and after their relationships; the women also recount instances of paternalism and naïveté present in civil and criminal courts. While their male abusers seemed to receive leniency from court officials, despite, in some cases, violating judges' direct orders, the women's efforts were sometimes interpreted as recalcitrance and disobedience when they challenged unfair labels, visitation, and custody decisions. This qualitative study contextualizes women's efforts and actions taken to safeguard their children during and after their relationships to highlight women's experiences the courts overlook and misconstrue as well as what happens when women engage with the courts. Policy suggestions include ways to prevent the continued victimization of battered women by the courts, to challenge the pejorative assessment of mother's protective behaviors, and to illuminate court officials' malfeasance and toleration of fathers' tactics.